Jozef Pilsudski : founding father of modern Poland - Zimmerman, Joshua D. (Harvard University Press, 2022)
"An authoritative biography of Jozef Pilsudski, a key figure in interwar Europe regarded as the founding hero of a pluralistic and democratic modern Poland. After the first elected president was assassinated, Pilsudski lost faith in Poles' commitment to democracy, led a military coup, and ruled as a strongman, leaving a complicated legacy"-- Provided by publisher.
Keywords: Piłsudski, Józef, -- 1867-1935.; Piłsudski, Józef, -- 1867-1935; Heads of state -- Poland -- Biography.; Poland -- History -- 1864-1918.; Poland -- History -- 1918-1945.; Chefs d'État -- Pologne -- Biographies.; Pologne -- Histoire -- 1864-1918.; Pologne -- Histoire -- 1918-1945.; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Heads of state; Poland; 1864-1945; Biographies; History